2014
DOI: 10.2478/10004-1254-65-2014-2527
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, Lead, and Mercury Exposure Assessment Among Croatian Consumers of Free-Living Game

Abstract: Free-living game can be an important source of dietary cadmium and lead; the question is whether exposure to these two elements is such that it might cause adverse health effects in the consumers. The aim of this study was to estimate dietary exposure to cadmium, lead, and mercury from free-living big game (fallow deer, roe deer, red deer, wild boar, and brown bear), and to mercury from small game (pheasant and hare), hunted in Croatia from 1990 to 2012. The exposure assessment was based on available literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Kicińska et al [15] reported a potential risk to health associated with the consumption of liver from game animals (HI > 1). In contrast, Lazarus et al [48] indicated that consumption of game meat and liver in Croatia did not pose a health risk to consumers, regardless of the exposure scenario. Nevertheless, the authors suggested that children should avoid eating game liver, because a high percentage of samples were found to exceed the permitted limits for Cd and Pb.…”
Section: Discussionmentioning
confidence: 91%
“…Kicińska et al [15] reported a potential risk to health associated with the consumption of liver from game animals (HI > 1). In contrast, Lazarus et al [48] indicated that consumption of game meat and liver in Croatia did not pose a health risk to consumers, regardless of the exposure scenario. Nevertheless, the authors suggested that children should avoid eating game liver, because a high percentage of samples were found to exceed the permitted limits for Cd and Pb.…”
Section: Discussionmentioning
confidence: 91%
“…In turn, red deer meat derived from Croatia contained ca. 0.1710 mg lead/kg meat [33]. Based on the collected data, it can be concluded that both the environmental conditions and the site of lead gunshot on animal body represent important factors that determine this element content in meat.…”
Section: Resultsmentioning
confidence: 90%
“…The permissible level of mercury in meat of slaughter animals has been set at 0.04 mg/kg meat. [33,36]. From the above data, including studies carried out at different times and in different places, it appears that -contrary to the popular belief -venison is not highly contaminated with heavy metals.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…4 MD, MSc, Centro de investigaciones Fundación Valle del Lili, Cali -Colombia, associated profesor at Universidad Libre Cali, Colombia. followed by pollution and breast milk or powdered formula in the newborns 2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%